MAKNA LAFAZH QAUL DAN KALí‚M DI DALAM AL-QUR'AN MENURUT PERSPEKTIF ILMU BALAGHAH - Murdiono, Murdiono; Hasaniyah, Nur; Taufiq, Hadi Nur (Arabi : Journal of Arabic Studies, 2021)
This study analyzes lafazh qaul and "kalām" in the Qur'an according to balāghah perspective, also discussing the meaning of the context of the two lafazhs. Because in balāghah's perspective, there is no same word, each lafazh has a different meaning even though it is the same in its textual form.  As ibtalā and ikhtabara mean to test. the word ibtalā is used for the meaning of good and bad trials. But the Arabs used it a lot for bad trials. While the word ikhtabara derived from the word khabara is used for the meaning of testing in a good context only. This literature research examines the use of the Qur'anic language in lafazh qaul and kalām and its meaning which aims to examine the miracles of the Qur'an in the aspect of language. The results of this study indicate that lafazh kalām is a part of qaul. Lafazh qaul and expressed in the context of something that is known or not known by humans, and qaul has two meanings, namely qaul mufīd and qaul ghairu mufīd. Meanwhile, lafazh kalām is devoted to the speech of Allah to the prophet, the speech of Allah to fellow human beings, and the speech of Allah to the dead.